Portuguese converted deverbal nouns: constraints on their bases - Rodrigues, Alexandra Soares (2011)
The aim of this paper is to analyse the constraints that govern the formation of Portuguese converted deverbal nouns (‘CDNs’). To this end, we have analysed a total of 1323 converted deverbal nouns. The first type of constraints investigated are those found at the prosodic level: these deal with the configurational formatting of the minimal root. We will focus on the relationship between these constraints and the semantic and phonological identification of the lexical item in perceptual terms. The second level of constraints may be characterised as morphophonological-pragmatic. Many verbs contain morphological units that block the formation of CDNs because their [+Latinate] character has a certain stylistic effect in terms of pragmatic usage. The third level of constraints pertains to lexical-conceptual structure combined with argument structure. We will show that (i) the constraints on the bases of CDNs are not exclusively founded on morphological incompatibilities between derivational affixes and other morphological units with which they join. Thus, a derivational mechanism that does not involve affixation, such as conversion, is also ruled by restrictions on the bases. (ii) Structural constraints – based on argument structures and on prosodic, morphological and lexical-semantic structures – are interwoven with processing and pragmatic conditions. (iii) Word formation is organised in structures that have interfaces with each other.